The Effect of on-Street Parking on Traffic Performance in Commercial Areas of Small Cities in Indonesia (Case Study: St. Merdeka Utara Cirebon) - Andhika Hikmawan Nur Iman; Fikri Hariwibowo; Rubangga Rubangga; Mira Lestira Hariani (Jurnal Indonesia Sosial Teknologi, 2025)
Street Parking is one of the factors that causes a decrease in traffic performance, especially in commercial areas of small cities, so it is necessary to organize it so traffic performance can remain by the planning. The purpose of this study was to find out what the impact of on-street parking traffic is on-road performance and to provide recommendations in the form of parking location arrangements. The calculation method used to analyze road performance is the Indonesian Road Capacity Guidelines (PKJI 2023) while parking utilizing the technique of the Director General of Land Transportation (1996). The results of the study showed that the presence of on-street parking at the study location resulted in road performance becoming Level Of Service (LOS) D and off-street parking resulted in road performance becoming Level Of Service (LOS) C. If on-street parking and off-street parking are not moved, the Level Of Service (LOS) value will be E and F. And this study is to provide recommendations for moving parking locations around traditional markets. In conclusion, parking rearrangements and relocation of parking locations can improve road performance and reduce congestion, with implications for more efficient transportation planning in small towns, especially around commercial areas and traditional markets.